Monthly forage value of various plant organs of Brocchia cinerea (Vis.) from a Moroccan arid region (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Chlif N, Diouri M, El Omari M, Bentayeb A. 2021. Monthly forage value of various plant organs of Brocchia cinerea (Vis.) from a Moroccan arid region. Biodiversitas 23: 67-74. Brocchia cinerea Vis (Asteraceae) represents a xerophytic botanical species widely used in South-Eastern Morocco as a potential animal feed. The present study was aimed to investigate the chemical profile, as well as the in vitro dry matter digestibility (IVDMD), and to estimate the net energy for lactation (NEl) of some fractions (flowers, leaves, stems, and browsable aerial part (whole part a 10 cm above the ground) of B. cinerea. The ether extract (EE) content of some plant parts varied between 0.43 and 1.89%. As far as, the highest concentration of crude protein (CP) was found in leaves. The maximal values for neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL) were found in the mature stems with 58.63%, 44.87%, and 13.05%, respectively. The leaves were the richest fraction in essential oil (EO), total phenols (TP), and tannins. Furthermore, the IVDMD values of various fractions of plants ranged between 59.56 to 89.43 %. The assessed NEl was highest during cold months in some fractions of young plants and decreased with maturity. In conclusion, B. cinerea has a good nutritive value, especially in leaves and early stages.